The Influence of Social Networks on Mental Health - Milošević, Slađana; Milošević, Dejana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2022)
Social networks are platforms that allow users of private and public profiles to have different types of interaction with other users. Given the increasing use of social networks, especially among the younger population, this paper aims to point out the impact of the use of social networks on mental health. A review of the relevant literature on the potential impact of social networks on mental health has been made. The use of social networks has advantages: establishing interpersonal relationships, personal and business relationships with others, sharing photos, expressing creativity, ideas and feelings, promoting health-related behaviour, and facilitating the interaction of shy and socially anxious individuals. However, the use of social networks is also associated with negative implications for mental health, such as the development of anxiety, feelings of loneliness, low self-esteem, depression and dependence on the use of social networks. Given the recognized negative implications of the use of social networks on the mental health of users, it is important to emphasize the need for continuous information on rational use to prevent negative outcomes, as well as the inevitable consideration of this factor in treating mental health problems.